Risk Priority Analysis for Change Management on E-Government using RIPC4 and AHP - Muhammad Nasrullah; Sayekti Harits Suryawan; Noerma Pudji Istyanto; Titus Kristanto (Universitas Bina Darma, 2022)
A project cannot be separated with the name of the risk, not the exception to the abstract information technology projects, and can only be perceived benefits in the long term. So, it becomes a very important thing to manage risk properly so helpful to the success of the project. In this paper, we contribute to the model in analyzing the priorities of risk to the project E-Government to adopt the model of risk assessment using RIPC4 and Analytic Hierarchy Process (AHP) in assessing the risk, so it can know which risks a priority to perform the procedure changes in the implementation of e-government based on the strategy used in the process of change management.